Strategi Pengembangan Pariwisata Kota Semarang (Studi Kasus Peningkatan Obyek Wisata Taman Margasatwa Semarang - Praniti, Dina Locita; Widowati, Nina; Subowo, Ari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
ABSTRACT One of the programs of tourist affair development which is managed by department of culture and tourism of Semarang City is developing tour destination especially developing the tourist area named â€œUpgrading the Semarang Zooâ€. Semarang Zoo area becomes one of flagship programs developed by the government because the area has a great potential to give its largest contribution for PAD. This study used descriptive qualitative method and strategic management theory in explaining appropriate strategic issues for Semarang Zoo development by using SWOT data analysis. The data are collected from interview, field notes , a photograph , documents and observation.The result of this research indicates that tourist area development at UPTD Semarang Zoo has not brought maximal result. It can be seen from the lack of facility maintenance, such as the dirty toilet, peopleâ€™s complaint of sleazy cage, incomplete facility, lack of socialization and promotion. Therefore, it is need new technology in managing and developing the tourist area at Semarang Zoo. For example there is no cage reconstruction but rather there are addition of animal collections, cleaning services and attraction to promote it